1997
DOI: 10.1017/s1014233900001012
|View full text |Cite
|
Sign up to set email alerts
|

Le Zébu Gobra: caractères ethniques et performances zootechniques

Abstract: This paper reviews the main results obtained in zebu Gobra cattle. Under the breeding conditions of C.R.Z. of Dahra, the average daily growth is 280 g but can reach 736 g in well fed males and 1 080 g in feed lots. Carcass traits are also good and compare favourably with those of specialized meat breeds. Age at first calving (1 365.6±24 days) and intervals between calvings (15.5 months) are high but can be reduced by improving breeding conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Summary statistics for LW, HG and HW for adult and heifers for the various breed groups are given in Missohou et al 1997). The average LW, HG and HW measures for cows of high Bos Taurus found in this study were generally lower compared to 419-781 kg, 176-223 cm and 125-150 cm reported for Holstein Friesians cows in a developed country context (Yan et al 2009), likely due to the lower feeding level of animals in this study in comparison to that in the developed world, and because the high Bos Taurus group in this study were not always pure-bred (see Table 1).…”
Section: Observed Body Measurements and Their Correlationsmentioning
confidence: 99%
“…Summary statistics for LW, HG and HW for adult and heifers for the various breed groups are given in Missohou et al 1997). The average LW, HG and HW measures for cows of high Bos Taurus found in this study were generally lower compared to 419-781 kg, 176-223 cm and 125-150 cm reported for Holstein Friesians cows in a developed country context (Yan et al 2009), likely due to the lower feeding level of animals in this study in comparison to that in the developed world, and because the high Bos Taurus group in this study were not always pure-bred (see Table 1).…”
Section: Observed Body Measurements and Their Correlationsmentioning
confidence: 99%
“…However, because of CRZ difficulties on data collection and herd management, these measurements have been gradually abandoned (Thiongane and Denis, 1974;Chollou et al, 1978;Sow et al, 1988;Sow et al, 1991). In rural farms, latest information was provided by Mime (1981), Pagot (1985) and Missohou et al (1997). In summary, recent morphometric informations on adult Gobra animals do not exist so it was not easy to compare our results.…”
Section: Discussion:-mentioning
confidence: 95%
“…The morphometric measurements for their part are lower than those available in the literature. Indeed, the study of Denis and Thiongane (1973) on zebu Gobra cattle enrolled in the CRZ of Dahra's breeding program, reported a HeW's average from 122 to 133 cm, Mime (1981) and Missohou et al (1997) described a HeW varying from 135 to 140 cm for the male and from 125 to 135 cm for the female. The sexual dimorphism with a marked superiority of males compared to females was early emphasized by Pagot (1985).…”
Section: Discussion:-mentioning
confidence: 99%
“…These performances are constrained by the environment, indicating the poor availability and quality of fodder. Indeed, while local breeds might present genetically lower performances due to their adaptation to scarcity, several studies showed that the genetic potential of indigenous breeds might be better exploited by the adoption of simple husbandry techniques, relating to feeding and health follow-up, resulting in higher weight gains and milk yields (Achard and Chanono, 1997;Missohou et al, 1997;N'Djoya and Loko, 1997).…”
Section: Reproduction Performancesmentioning
confidence: 99%